REKONSTRUKSI RELASI ANTAR LEMBAGA LEGISLASI DI INDONESIA - Sorik, Sutan (UI Scholars Hub, 2021)
This study discusses the reconstruction of relations between legislative institutions in Indonesia. This study aims to find the ideal relations of the Regional Representative Council(DPD), the House of Representatives (DPR), and the President in the formation of laws in Indonesia, as an effort to produce laws that have efficacy and usefulness. The type of research used in this study is normative juridical research. From the analysis found that the authority of the DPD is constitutionally only optional and has no imperative power, which then has implications for the relations between the DPD and the DPR and the President in shaping the law. The DPD in the formation of the law is onlyused as a complementary legislative body. This shows that there are inconsistencies and incoherence with the aim of democratizing legislative institutions, the principles of popular sovereignty, check and and balances, and the bicameral system. The results of this study recommend purification of the relations between DPD, DPR and the President. Revitalizing the position, role, authority and power ofthe DPD to have original power.